Pengembangan Beras Jagung dan Penyusunan SOP Penanakan menggunakan Rice Cooker - Tjahja Muhandri; Subarna Subarna (IPB University, 2011)
Research on rice substitution has been done, but it is difficult in application. The objectives of this research were to study the corn rice technology and to design the standard operating procedure (SOP) of corn rice cooking. This research used P21 corn variety, polisher, breaker roll, shiver and rice cooker. Corns were crushed, polished, and shivered in to 5 sizes (>4 mm, 3.35-4 mm, 2.36-3.35 mm, 1.18-2.36, dan <1.18 mm). A part of corn grits were cooked straightly, another part were soaked before cooking. The survey result showed that consumers preferred 1.18-2.36 mm corn grits. Corn grits of <1.18 mm and 1.18-2.36 mm, can be cooked using rice cooker without pre-soaking. Corn grits of >4 mm, 3.35-4 mm, and 2.36-3.35 mm should be soaked before cooked using rice cooker. Nutrition content of corn grits were 79.08% of carbohydrates, 6.80% of protein, 1.1%of lipid, 15.48% of dietary fiber, 0.25% of ash, and 353.38 kcal of calorie.Keyword : corn rice, cooked, rice cooker